SCHNITZLER:REIGEN (2BD.E) E-BOOK OA Historisch-kritische Ausgabe - Rauchenbacher, Marina (De Gruyter, 2021)
La Ronde is one of Arthur Schnitzler’s most controversial works. The historical-critical edition provides an introduction to its history, reconstructs the provenance of the manuscript, and presents a facsimile of the manuscript along with a transcription, a print text, and a commentary. The edition offers a new foundation for the study of the central text in Schnitzler’s oeuvre.